Universidade, desenvolvimento regional e empreendedorismo: uma relação de imanência - Righi, Moacir Luiz (2012)
This study has as main theme relate the importance of entrepreneurship to regional development. For this, the general aim was to identify entrepreneurial activities in the creation and expansion of UFSM and its influence on expansion of higher education and the economy of the city of Santa Maria. To achieve this objective the research was divided into three stages, each of these is presented in the format of a scientific paper. The first paper identifies entrepreneurial actions that led to the creation of UFSM with the structure model used. The second paper seeks to relate the growth of UFSM with the development of other institutions of higher education in Santa Maria. The third establishes a relationship between the growths of UFSM with GDP growth of Santa Maria. The results demonstrate the importance of UFSM to form a center of higher education and economic development of Santa Maria.